1998
DOI: 10.1073/pnas.95.5.2458
|View full text |Cite
|
Sign up to set email alerts
|

CD81 on B cells promotes interleukin 4 secretion and antibody production during T helper type 2 immune responses

Abstract: Mice lacking CD81 (TAPA-1), a widely expressed tetraspanin molecule, have impaired antibody responses to protein antigens. This defect is specific to antigens that preferentially stimulate a T helper 2 response (ovalbumin or keyhole limpet hemocyanin in alum) and is only seen with T cell-dependent antigens. Absence of CD81 on B cells is sufficient to cause the defect. Also, antigen-specific interleukin (IL) 4 production is greatly reduced in the spleen and lymph nodes of CD81-null mice compared with heterozygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 39 publications
2
65
0
Order By: Relevance
“…It is widely expressed and has been shown to influence numerous cellular functions in the immune and nervous systems (1)(2)(3)(4)(5). More recently, CD81 has been shown to be required for membrane reorganization during fertilization: cd81 Ϫ/Ϫ eggs do not fuse with wild-type (WT) 3 sperm, resulting in female infertility, a similar defect has been described in CD9-deficient mice (Ref.…”
mentioning
confidence: 89%
“…It is widely expressed and has been shown to influence numerous cellular functions in the immune and nervous systems (1)(2)(3)(4)(5). More recently, CD81 has been shown to be required for membrane reorganization during fertilization: cd81 Ϫ/Ϫ eggs do not fuse with wild-type (WT) 3 sperm, resulting in female infertility, a similar defect has been described in CD9-deficient mice (Ref.…”
mentioning
confidence: 89%
“…Although CD81-deficient mice exhibit normal maturation of all lymphoid cells, they show a decreased Ab production in response to protein Ags (12,13). Hence, chimeric mice in which only B cells lacked CD81 have reduced Ab production upon exposure to a Th2 stimulus (14). Lately, it has been reported that CD81…”
mentioning
confidence: 99%
“…In this regard, several studies have emphasized the role of the tetraspanin CD81 in promoting a potent costimulatory signal to T cells (6) and in controlling sustained T cell signaling and molecular organization of the immune synapse (7). Additionally, whereas lymphoid development in CD81 2/2 mice is normal (8)(9)(10), T cells from CD81 2/2 mice present a hyperproliferative phenotype after anti-CD3 stimulation and impaired development of Th2 responses (8,11).…”
mentioning
confidence: 99%